Joint Modulation and Coding Scheme Toward Low-Complexity WBAN System - Oh, Mi-Kyung; Jeong, Jin-Doo; Lee, HyungSoo (IEEE communications letters, 2011)
This letter proposes a new pulse position modulation (PPM) combined with coding scheme for wireless body area network (WBAN) system. By utilizing redundant time slots in grouped PPM symbols, we incorporate a low-complexity block code to achieve coding gain without bit-rate reduction. Simulations and FPGA elaboration verify the proposed joint modulation and coding scheme.